2008
DOI: 10.12973/ejmste/75348
|View full text |Cite
|
Sign up to set email alerts
|

Technology in Learning: Narrowing the Gender Gap?

Abstract: The introduction of Information and Communication Technology (ICT) into the school curricula raised some hopes that it could minimize gender differences in learning. The interactive nature of ICT materials was believed to provide a favorable environment especially for girls to learn. This article reports the findings of the study that analyzed students' gender differences in learning using computers in Botswana junior secondary schools in the year 2006. Variables considered were usefulness and enjoyment of usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 16 publications
0
11
1
1
Order By: Relevance
“…High anxiety in girls, as reported by Baloğlu and Çevik (2008), Kaino (2008), Adebowale et al (2009), andKubiatko et al (2011), and girls' low self-confidence, as reported by Volman and Van Eck (2001), Ogan et al (2005), or Christoph et al (2015), may contribute to a low achievement of digitals skills. On the other hand, enjoyment seems to be similar for both genders, according to Ogan et al (2005), Fančovičová and Prokop (2008), Kaino (2008), Teo (2008), and Adebowale et al (2009) but higher in girls than in boys at early ages (Kubiatko et al, 2011). We believe it is relevant to know whether this is also the situation of the Catalan students at the beginning of secondary education or not and to consider taking advantage of this enjoyment to develop more entertaining and effective ICT activities.…”
Section: Figure 1 Percentage Of Females (In Dark Grey) and Males (Inmentioning
confidence: 89%
See 4 more Smart Citations
“…High anxiety in girls, as reported by Baloğlu and Çevik (2008), Kaino (2008), Adebowale et al (2009), andKubiatko et al (2011), and girls' low self-confidence, as reported by Volman and Van Eck (2001), Ogan et al (2005), or Christoph et al (2015), may contribute to a low achievement of digitals skills. On the other hand, enjoyment seems to be similar for both genders, according to Ogan et al (2005), Fančovičová and Prokop (2008), Kaino (2008), Teo (2008), and Adebowale et al (2009) but higher in girls than in boys at early ages (Kubiatko et al, 2011). We believe it is relevant to know whether this is also the situation of the Catalan students at the beginning of secondary education or not and to consider taking advantage of this enjoyment to develop more entertaining and effective ICT activities.…”
Section: Figure 1 Percentage Of Females (In Dark Grey) and Males (Inmentioning
confidence: 89%
“…The level of enjoyment has been widely reported as being similar for boys and girls (Adebowale et al, 2009;Fančovičová & Prokop, 2008;Kaino, 2008;Ogan et al, 2005;Teo, 2008). However, some authors point at higher levels of enjoyment in boys than in girls (Fraillon et al, 2014).…”
Section: Attitudes and Self-efficacymentioning
confidence: 94%
See 3 more Smart Citations